Present state and future prospects of the environment in Latin America and the Caribbean. - GLIGO, Nicolo (1995)
Explores the concept that the region's environment and natural resources constitute the weakest link in its development strategies. Concludes that the region's environmental problems can only be solved by a number of different approaches : political, social, economic, anthropological, scientific and technological.